2012
DOI: 10.1016/j.jcrs.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with flap amputation, phototherapeutic keratectomy, and collagen crosslinking in severe intractable post-LASIK atypical mycobacterial infection with corneal melt

Abstract: A 23-year-old woman was referred for management of intractable post-laser in situ keratomileusis (LASIK) keratitis due to atypical mycobacteria in the left eye. Corrected distance visual acuity was 20/20 in the right eye and counting fingers at 3 meters in the left eye. Slitlamp examination revealed multiple infiltrates in the flap interface and severe corneal stromal melting with thinning. Despite maximum antibiotic therapy for 7 days, the keratitis continued to worsen. A penetrating keratoplasty (PKP) was sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
(30 reference statements)
0
13
1
Order By: Relevance
“…Thus, it increases resistance against microbial degradation and corneal melting (26,(35)(36) . Even though some clinical trials and experimental studies have shown improvement of fungal ulcers with CXL (21,23) , this was not observed in our study. All of our patients with fungal ulcers underwent adjuvant surgical treatment aimed at curing the infectious process.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Thus, it increases resistance against microbial degradation and corneal melting (26,(35)(36) . Even though some clinical trials and experimental studies have shown improvement of fungal ulcers with CXL (21,23) , this was not observed in our study. All of our patients with fungal ulcers underwent adjuvant surgical treatment aimed at curing the infectious process.…”
Section: Discussioncontrasting
confidence: 91%
“…Studies show that therapeutic transplants represent 2.6% to 17.9% of total penetrating transplants (17) . There are reports of corneal ulcers treated successfully with corneal collagen crosslinking (CXL) (18)(19)(20)(21)(22)(23)(24)(25) . An experimental study found increased resistance to enzymatic digestion by collagenase, pepsin, and trypsin in corneas subjected to CXL (26) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Planned therapeutic flap amputation has been reported in cases of recalcitrant epithelial ingrowth or infectious keratitis not responding to conservative therapy. [7][8][9] In most cases with flap or interface complications, concerted attempts are made to preserve the flap, even in cases of late dislocation. We are not aware of any reports of planned flap amputation for irregular astigmatism or flap-specific opacity.…”
Section: Discussionmentioning
confidence: 99%
“…16 Corneal remodeling occurs for several months after the procedure 4 ; therefore, an additional laser procedure, such as PRK, should not immediately follow the flap amputation. 9 Phototherapeutic keratectomy may be performed to smooth corneal irregularities caused by variations in corneal thickness, which can improve refractive outcomes. The epithelium has a tremendous capacity to compensate for irregular curvature [17][18][19] ; thus, direct epithelial measurements will benefit direct determination of stromal surface topography to guide optimal therapeutic ablations and may improve outcomes.…”
Section: Discussionmentioning
confidence: 99%